Trends in Infectious Diseases 2014
DOI: 10.5772/57574
|View full text |Cite
|
Sign up to set email alerts
|

Oral HPV Related Diseases: A Review and an Update

Abstract: Please use Adobe Acrobat Reader to read this book chapter for free. Just open this same document with Adobe Reader. If you do not have it, you can download it here. You can freely access the chapter at the Web Viewer here. inhibitors. This may explain the huge variation in HPV detection rate: 22 to 60% or 0 to 81.1%, depending on the methods and on the studied population [15]. Recent meta-analysis has demonstrated that HPV is an isolated risk factor for the development of oral carcinoma [2]. Oral squamous cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 68 publications
(200 reference statements)
0
2
0
Order By: Relevance
“…Recurrences are quite common and reported in 20%–30% of patients undergoing treatment which may occur in same or different locations 14. According to some authors, recurrence may be due to the long incubation period of HPV (2–3 months) which can result in new lesions and/or by subsequent infection with the same or different subtypes of the virus through autoinoculation or transmission from other persons 13…”
Section: Discussionmentioning
confidence: 99%
“…Recurrences are quite common and reported in 20%–30% of patients undergoing treatment which may occur in same or different locations 14. According to some authors, recurrence may be due to the long incubation period of HPV (2–3 months) which can result in new lesions and/or by subsequent infection with the same or different subtypes of the virus through autoinoculation or transmission from other persons 13…”
Section: Discussionmentioning
confidence: 99%
“…She presented no recurrence during 2 years of follow-up. Improvements in adherence to HAART may lead to a reduction in HPV oral lesions (dos Reis et al, 2014;Dos Reis et al, 2009;Ferraro et al, 2011), although some studies have suggested that the prevalence of HPV oral lesions may increase in the HAART era (Anaya-Saavedra et al, 2013) due to immune reconstitution inflammatory syndrome (Shiboski et al, 2016…”
mentioning
confidence: 99%